2019
DOI: 10.1111/tmi.13242
|View full text |Cite
|
Sign up to set email alerts
|

Day clinic vs. hospital care of pneumonia and severe malnutrition in children under five: a randomised trial

Abstract: Summary Objectives To evaluate the clinical outcomes and costs of managing pneumonia and severe malnutrition in a day clinic (DC) management model (outpatient) vs. hospital care (inpatient). Methods Randomised clinical trial where children aged 2 months to 5 years with pneumonia and severe malnutrition were randomly allocated to DC or inpatient hospital care. We used block randomisation of variable length from 8 to 20 and produced computer‐generated random numbers that were assigned to one of the two intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 15 publications
0
18
0
3
Order By: Relevance
“…We analyzed the data by using SPSS for Windows (version 21.0; SPSS Inc., Chicago, IL, USA) and Epi Info (version 7.0, USD, Stone Mountain, GA, USA). On the basis of previous study findings [ 23 , 24 , 25 ], we assumed the clinical outcome of day-cares and hospitals would be similar, and therefore, we analyzed the data together to compare the malnourished and well-nourished children, and we did not compare the outcome of clinical features among day-cares versus hospitals in our study. As day-cares and hospitals were used for the same protocols for the management/treatment of children with severe pneumonia, we did not consider it as a variable, and for that reason, it was not analyzed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed the data by using SPSS for Windows (version 21.0; SPSS Inc., Chicago, IL, USA) and Epi Info (version 7.0, USD, Stone Mountain, GA, USA). On the basis of previous study findings [ 23 , 24 , 25 ], we assumed the clinical outcome of day-cares and hospitals would be similar, and therefore, we analyzed the data together to compare the malnourished and well-nourished children, and we did not compare the outcome of clinical features among day-cares versus hospitals in our study. As day-cares and hospitals were used for the same protocols for the management/treatment of children with severe pneumonia, we did not consider it as a variable, and for that reason, it was not analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier efficacy trials have reported primary health care facilities equipped with oxygen, pulse oximeter, suction machine, and nebulizer facilities can provide efficient care for severe pneumonia irrespective of the nutritional status of the children on a day-care basis if staff were provided with quality clinical management training [ 23 , 24 , 25 ]. Such facilities provided care and treatment to the children on an outpatient basis, during daytime hours, and sent the children home with advice to return the following day until an outcome (recovery or referral to the hospital) was achieved [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Penyakit lain seperti pneumonia menyumbang kematian pada anak dengan malnutrisi hingga 23% atau 15 kali lebih besar (7) . Penyakit infeksi lainnya sebanyak 68,5% juga mengambil bagian penyebab peningkatan kejadian malnutrisi didapat di rumah sakit (8) .…”
Section: Abstrakunclassified
“…Malnutrisi didapat di rumah sakit memiliki kelebihan dan kekurangan dalam hal penanganan dan manajemen pemberian terapi. Salah satu kelebihannya adalah 86% asuhan manajemen nutrisi yang diberikan oleh profesional ahli di rumah sakit tertangani dengan baik dibandingkan klinik mulai dari penanganan triase, pengawasan dan pemantauan status nutrisi yang tepat serta rujukan bila diperlukan (7) . Namun adanya infeksi nosokomial di rumah sakit akibat lama rawat anak selama masa hospitalisasi akan memperburuk kondisi anak.…”
Section: Metodeunclassified
See 1 more Smart Citation